Herbicide association for simultaneous control of seeds and emerged plants of Rottboellia exaltata L. (Research, Society and Development, 2023)
The species Rottboellia exaltata L. (itchgrass) has become an important weed in cultivated areas, requiring management studies to enhance its control. This study aimed to evaluate the effectiveness of the herbicides pendimethalin (1200 g ha−1), clomazone (1000 g ha−1), indaziflam (100 g ha−1), and trifluralin (900 g ha−1) applied in pre-emergence in association with diquat (400 g ha−1) and glyphosate (1175 g ha−1), in addition to their isolated application, in the simultaneous control of emerged plants and seeds of R. exaltata. The experiments were conducted in a greenhouse in a completely randomized design, with four replications. Evaluations were performed at 7, 14, 21, 28, 35, and 42 days after application (DAA). The associations of diquat + pendimethalin, diquat + clomazone, diquat + indaziflam, diquat + trifluralin, glyphosate + pendimethalin, glyphosate + clomazone, glyphosate + indaziflam, and glyphosate + trifluralin controlled 100% of the species and prevented the germination of new fluxes of R. exaltata. Regarding isolated applications, only clomazone did not differ from herbicide associations in controlling the species. Thus, the interaction promoted by the association between desiccant and residual herbicides was the best option to control R. exaltata, consisting of an important management tool to control the species, considering the post-emergence control and the seed bank.